Favourable Pregnancy Outcomes Recorded amongst Teenagers Delivered in a Teaching Hospital Annex in Southwestern Nigeria – Report of a 10-year Retrospective Review - Oluseun Oloruntoba Adeko; Adekunle Joseph Ariba; Victoria Iyabo Olafimihan; Alarape Naomi Oluwasanya (Nigerian Journal of Medicine)
Context: Teenage pregnancy has been established as high risk associated with adverse outcomes. However, some authors have posited that these can be significantly reduced with provision of antenatal care (ANC) and supervised deliveries by skilled personnel. Aims: To determine the incidence of teenage pregnancy at the Saje annex of Olabisi Onabanjo University Teaching Hospital and describe the sociodemographic and obstetric characteristics of the mothers, as well as the maternal and newborn outcomes. Settings and Design: This was a 10-year retrospective review of pregnancies and deliveries of teenage mothers between January 2010 and December 2019. Subjects and Methods: The data were collected with an electronic Google Form. Study outcomes were mode of delivery, booking status and post-partum haemorrhage (PPH) for the mothers; birth weight, estimated gestational age (EGA) at delivery and foetal status at birth for the babies. Statistical Analysis Used: Descriptive statistics was used to analyse the data. Results: Of 1858 deliveries during the study period, 49 (2.63%) were teenagers (26.3 per 1000 births). Majority (71.4%) of them were married, educated up to secondary level (91.8%) and 46.9% were employed. Their mean height was 160.3 ± 6.0 cm and none was short stature. As many as 91.8% were booked for ANC and 45 (91.8%) had vaginal deliveries with no PPH recorded. The mean birth weight of the babies was 2.77 ± 0.54 kg with 9 (18.4%) having low birth weight. Eleven (22%) of the babies were preterm with only one (2.0%) stillbirth recorded. Conclusions: The teenagers in this study achieved relatively impressive pregnancy outcomes. Identified contributory factors were optimal height, secondary education, access to ANC and availability of skilled obstetric care.